2018
DOI: 10.1007/s11011-018-0322-3
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase: a potential biomarker for stroke and implications for treatment

Abstract: Stroke is the fifth leading cause of death in the U.S., with more than 100,000 deaths annually. There are a multitude of risks associated with stroke, including aging, cardiovascular disease, hypertension, Alzheimer's disease (AD), and immune suppression. One of the many challenges, which has so far proven to be unsuccessful, is the identification of a cost-effective diagnostic or prognostic biomarker for stroke. Alkaline phosphatase (AP), an enzyme first discovered in the 1920s, has been evaluated as a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 179 publications
0
43
0
Order By: Relevance
“…Our findings on a variation in ALP over time might be particularly interesting since ALP has been reported to be strongly associated with the development of the MetS in healthy subjects, irrespectively of the liver dysfunction [ 48 , 49 ]. This link could be explained with a possible role of ALP as a marker of visceral obesity and inflammation, and ALP level might predict CVD, development of MetS, and mortality in the general population [ 49 , 50 ]. Our data further support the importance of the observation of ALP as a marker of metabolic risk in clinical practice, emphasizing a preventive role of the citrus supplement.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on a variation in ALP over time might be particularly interesting since ALP has been reported to be strongly associated with the development of the MetS in healthy subjects, irrespectively of the liver dysfunction [ 48 , 49 ]. This link could be explained with a possible role of ALP as a marker of visceral obesity and inflammation, and ALP level might predict CVD, development of MetS, and mortality in the general population [ 49 , 50 ]. Our data further support the importance of the observation of ALP as a marker of metabolic risk in clinical practice, emphasizing a preventive role of the citrus supplement.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al found that increased ALP levels were associated with the presence of cerebral small vessel disease 40) . These basic and clinical findings might indicate that ALP plays a role in the blood-brain barrier (BBB) breakdown, neuroinflammation, and vascular dysfunction in stroke patients 41) . The mechanisms underlying the associations between increased ALP levels, neuroinflammation, BBB permeability, and vascular homeostasis might contribute to poor stroke outcomes 41) .…”
Section: Disclosuresmentioning
confidence: 94%
“…ALPL plays a crucial role in intracellular signaling and regulation of protein activity [ 6 8 ]. Dysfunction of this enzyme is related to the development of multiple diseases, including diabetes mellitus, liver disease, stork and Alzheimer’s disease [ 9 12 ]. According to recent reports, ALPL also plays a role in cancer.…”
Section: Introductionmentioning
confidence: 99%